Pemanfaatan Limbah Pouch Kopi sebagai Bahan Baku Produk Ramah Lingkungan: (Studi Kasus pada Demibumi dan Brookland Coffee) - Dinda Kusuma Gunawan; Evelyn Veronica; Karren Gracia (International Forum of Researchers and Lecturers, 2025)
Based on data from the United States Department of Agriculture (USDA), global coffee production reached 170 million bags per 60 kg of coffee during the 2022/2023 period. Indonesia is noted as one of the largest coffee-producing countries in the world in 2023. The plastic packaging waste from coffee shops is increasing, posing a potential threat to environmental sustainability, such as soil and water pollution. According to Bizhare Contributor in 2023, the Food and Beverage industry in Indonesia has already reduced plastic waste, but there are still plastic packaging, particularly for coffee beans, that cannot be replaced with environmentally friendly materials. From this, the problem of this research is